PERSPEKTIF EKONOMI ISLAM DALAM SUSTAINABLE DEVELOPMENT PADA PRODUKTIVITAS PETANI PEDESAAN - Budhijana, R Bambang (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2010)
This study aims to observe the development of farmer institutions and productivity in the aspects of sustainable development. This research was conducted in Karawang regency and Indramayu for 3 months between the months of May to July 2010. Research findings show the establishment of mutual trust. Â The trust is the result of interactions involving farmer productivity and their community. In these communities may contain contradictions in term of social competition, ego-sectoral without presenting technological innovation. Farmer institutions and productivity in the aspects of sustainable development usually cover economic institutional (E), Sharia Compliance (C), Cultural and Environment (B) and Government Policies (K). Rural communities have a strong social capital. Several indicators of social capital in improving of natural resources is to strengthen solidarity, social management, networking, social structure and the local community cooperativeness. Instead of social capital, the economic development is more influenced by society's ability to allocate natural resources, human capital and spiritual capital (like good moral values and ethics). However, social capital, human capital and the spiritual capital will productively have mutual trust, mutual respect and mutual benefit which are more extensive.